PENERAPAN HAZARD IDENTIFICATION RISK ASSESMENT AND MITTIGATION (HIRM) PADA PENGGUNAAN LABORATORIUM WORKSHOP POLITEKNIK PENERBANGAN MEDAN - Saut Maruli Manurung; Rivan Daniel Malau; Adolf Valentino Simanungkalit; Liber Tommy Hutabarat; Natanael Riansa Bakkara; Yesaya Swabra (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract This study discusses the implementation of the Hazard Identification, Risk Assessment, and Mitigation (HIRM) system at the Electrical Workshop Laboratory of Politeknik Penerbangan Medan as part of efforts to create a safe practice environment and foster a culture of occupational safety from an early stage. The laboratory serves as a facility for students to perform practical electrical engineering activities such as soldering, panel assembly, electrical measurements, and handling heavy equipment—activities with inherently high safety risks. The research applies the HIRM approach through stages of hazard identification, risk assessment using a probability and severity matrix based on ICAO Doc 9859 standards, and the formulation of mitigation strategies. Results identified seven main activities with moderate to high-risk levels. The highest risks were found in electrical installation assembly, battery testing, and distribution panel work, which can cause electric shock or serious injuries. Recommended mitigation includes the use of personal protective equipment (PPE), regular safety training, strict implementation of standard operating procedures (SOPs), and increased instructor supervision. The study concludes that HIRM is effective for implementation in vocational education settings, particularly in electrical engineering fields, and recommends the future development of digital monitoring systems for real-time risk assessment and improved laboratory safety management.. Keywords:   HIRM, Occupational Safety, Workshop Laboratory, Risk Assessment,                   Hazard Mitigation Abstrak: Penelitian ini membahas penerapan sistem Hazard Identification, Risk Assessment, and Mitigation (HIRM) di Laboratorium Workshop Kelistrikan Politeknik Penerbangan Medan sebagai bagian dari upaya menciptakan lingkungan praktik yang aman dan mendukung budaya keselamatan kerja sejak dini. Laboratorium ini digunakan oleh mahasiswa untuk kegiatan praktik kelistrikan seperti penyolderan, perakitan panel, pengujian alat ukur, dan pengangkatan peralatan berat yang memiliki potensi risiko tinggi. Penelitian dilakukan dengan pendekatan HIRM melalui tahapan identifikasi bahaya, penilaian risiko menggunakan matriks probabilitas dan keparahan berdasarkan standar ICAO Doc 9859, serta penyusunan langkah mitigasi. Hasilnya menunjukkan tujuh aktivitas utama dengan tingkat risiko sedang hingga tinggi. Risiko tertinggi terdapat pada perakitan instalasi listrik, pengujian baterai, dan pemasangan panel distribusi yang dapat menyebabkan sengatan listrik atau luka serius. Mitigasi yang disarankan mencakup penggunaan alat pelindung diri (APD), pelatihan keselamatan kerja, penerapan SOP, serta peningkatan pengawasan dosen. Studi ini menyimpulkan bahwa sistem HIRM efektif untuk diimplementasikan di lingkungan pendidikan vokasi teknik, khususnya pada bidang kelistrikan, dan ke depan perlu dikembangkan sistem monitoring digital berbasis teknologi informasi untuk penilaian risiko secara real-time.  Kata kunci: HIRM, Keselamatan Kerja, Laboratorium Workshop, Penilaian Risiko,                    Mitigasi Bahaya